Factors Influencing Post-Stroke Cognitive Impairment in Patients with Type 2 Diabetes Mellitus - Ma ZY; Wu YY; Cui HY; Yao GY; Bian H (Clinical Interventions in Aging, 2022)
Zhao-Yin Ma,1,* Yong-Ya Wu,2,* Hong-Yin-Long Cui,3 Guang-Yan Yao,3 Hong Bian3,4 1Department of Diagnostic, Medical Integration and Practice Center, Shandong University, Jinan, Shandong, People’s Republic of China; 2Department of Emergency Critical Care Medicine, The Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of China; 3Department of Neurology, Central Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 4Department of Neurology, Jinan Central Hospital, Shandong University, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Bian, Department of Neurology, Central Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China, Tel +86-15318816109, Fax +86-053188382085, Email jnbianh@163.comObjective: Type 2 diabetes mellitus (T2DM) and ischemic stroke, which are common diseases among older people, are closely related to cognitive impairment. This study aims to investigate the influencing factors of post-stroke cognitive impairment (PSCI) in patients with T2DM.Methods: We enrolled 161 patients with T2DM who experienced acute ischemic stroke and were hospitalized in the Department of Neurology, Jinan Central Hospital, Shandong, China. Cognitive function was evaluated with the Montreal Cognitive Assessment scale. According to the results, patients were divided into three groups—the cognitively normal group, mild cognitive impairment group, and severe cognitive impairment group. We analyzed general demographic data, laboratory information, imaging data, the results of neuropsychological evaluation, and clinical features as well as influencing factors of PSCI in these patients and established a prediction model.Results: The three groups of patients were significantly different in terms of age, education level, course of diabetes mellitus (DM), recurrent cerebral infarction (RCI), and other factors. RCI, course of DM, and glycated hemoglobin (HbA1c) were independent risk factors of PSCI in patients with T2DM, with odds ratio (95% confidence interval): 7.17 (2.09, 30.37), 5.39 (2.40, 14.59), and 3.89 (1.66, 10.04), respectively, whereas female, senior high school, serum albumin were protective factors: 0.28 (0.07, 0.95), 0.05 (0.01, 0.21), 0.20 (0.08, 0.42), respectively. Furthermore, we constructed a prediction model using sex, age, education level, RCI, DM course, HbA1c and serum albumin and obtained a receiver operating characteristic (ROC) curve. The area under the ROC curve is 0.966, suggesting the significant association of these influencing factors with PSCI in patients with T2DM.Conclusion: In this study, the occurrence of PSCI in patients with T2DM was related to RCI, course of DM, and HbA1c, among other factors. Attention to influencing factors is needed in these patients for early diagnosis and timely intervention of cognitive impairment.Keywords: blood glucose, cognitive impairment, ischemic stroke, risk factor